A new switching look-up table for direct power control of grid connected 3L-NPC PWM rectifier - Azziddin M. Razali; Nor Azizah Yusoff; Kasrul Abdul Karim; Auzani Jidin; Tole Sutikno (Institute of Advanced Engineering and Science, 2021)
This paper presents a comprehensive and systematic approach in developing a new switching look-up table for direct power control (DPC) strategy applied to the three-phase grid connected three-level neutral-point clamped (3L-NPC) pulse width modulated (PWM) rectifier. The term of PWM rectifier used in this paper is also known as AC-DC converter. The approach provides detailed information regarding the effects of each multilevel converter space vector to the distribution of input active and reactive power in the converter system. Thus, the most optimal converter space vectors are able to be selected by the switching look-up table, allowing smooth control of the active and reactive powers for each sector. In addition, the proposed DPC utilizes an NPC capacitor balanced strategy to enhance the performance of front-end AC-DC converter during load and supply voltage disturbances. The steady state as well as the dynamic performances of the proposed DPC are presented and analyzed by using MATLAB/Simulink software. The results show that the AC-DC converter utilizing the new look-up table is able to produce almost sinusoidal line currents with lower current total harmonic distortion, unity power factor operation, adjustable DC-link output voltage and good dynamic response during load disturbance.